Intra‐active refractions. Issue 1 (26th March 2021) - Pryor, Adam
Abstract: Responding to the analyses that Andreas Losch and Lucas John Mix offer regarding Living with Tiny Aliens: The Image of God for the Anthropocene, this article begins to address how their respective concerns regarding ratiocentric and anthropocentric ideas haunt the construction of a planetary account of the imago Dei . The article then introduces a subsequent line of critique not mentioned by Losch or Mix related to decentering the human individual from accounts of the imago Dei in order to highlight an ongoing challenge for transdisciplinary theological projects that involve astrobiology.